Indications of Hate Speech in the Speech Acts of Panji Gumilang on the Kick Andy Talk Show on Metro TV: A Forensic Linguistic Study - Mardhatillah, Siti Masyitha; Agustina, Agustina (JOLLT Journal of Languages and Language Teaching, 2025)
Recently, the Indonesian public has been stirred by various comments regarding several videos showing religious activities at Al-Zaytun Islamic Boarding School, which were considered deviating from religious teachings. These public comments sparked a response from the school's leader (PG), which was found to contain hate speech that was even more shocking. Therefore, this study aims to "uncover the types of hate speech found in PG's statements and critically analyze them through linguistic units as the means of delivery." This research employs a qualitative-quantitative approach and a descriptive-exploratory method, with the data object being PG's clarification statements during a Talk Show event.Based on the data analysis, the following results were obtained: First, six types of hate speech were identified in PG's statements, namely: (1) provocation (27%), (2) defamation (20%), (3) incitement (20%), (4) blasphemy (17%), (5) insult (15%), and (6) spreading fake news (1%). Second, the hate speech was conveyed through four types of linguistic units: (1) sentences (77%), (2) phrases (16%), (3) clauses (4%), and (4) words (3%). Based on these findings, it can be concluded that the dominant form of hate speech expressed by PG is through the use of sentences. This type of speech is primarily aimed at defending and justifying his belief that the religious policies and activities at the Islamic Boarding School he leads do not violate religious teachings and do not harm other parties or institutions.